Pelatihan Komunikasi Efektif untuk Service Excellence - Siti Dewi Sri Ratna Sari (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
This training activity aims to increase the insight of homestay managers in Tanjungjaya Village, Pandeglang Regency, Banten Province so that they can understand how to communicate effectively for service excellence to their homestay guests. Tanjungjaya Village is a tourism village that is frequently visited by domestic and foreign tourists, therefore homestay managers in this village need better communication skills. The method used in this activity is in the form of a short training on effective communication for service excellence. The training activities carried out for the participants were the explanation of material and case studies, followed by the question and answer session and the discussion. Participants of this training activity can attend the training well and enthusiastically, and they begin to understand how to communicate more effectively to customers. Keywords: Effective communication, service excellence, homestay, tourism village